The Political vs. the Theological: The Scope of Secularity in Arendtian Forgiveness - Lee, Shinkyu (Journal of religious ethics, 2022)
The conventional interpretation of Hannah Arendt's accounts of forgiveness considers them secularistic. The secular features of her thinking that resist grounding the act of forgiving in divine criteria offer a good corrective to religious forgiveness that fosters depoliticization. Arendt's vision of free politics, however, calls for much more nuance and complexity regarding the secular and the religious in realizing forgiveness for transitional politics than the secularist rendition of her thinking allows. After identifying an area of ambiguity in Arendt's thoughts that invites further investigation of religious forgiveness, this study seeks to relieve her misgivings about religion's role in politics by engaging with Dietrich Bonhoeffer's theology, which emphasizes worldliness and altruism in religious faith. Through constructive engagements with both thinkers, the article presents a balanced Arendtian position that is neither solely secularist nor complacent about religion in politics.